Geopolitical Perspectives and Technological Challenges for Sustainable Growth in the 21st Century : Proceedings of the 6th International Conference on Economics and Social Science - Dima Mihaela Alina (Sciendo, 2023)
The International Conferences on Economics and Social Sciences (ICESS)organized by Bucharest University of Economic Studies provide an opportunity for all those interested in Economics and Social Sciences to discuss and exchange research ideas. The series (ISSN 2704-6524) is aimed at publishing a selection of the peer-reviewed articles presented at the International Conference on Economics and Social Sciences (ICESS), organized yearly by the Bucharest University of Economic Studies, Romania. Each volume is associated with a particular edition of the conference. Date and location: June 15-16, 2023. Bucharest, Romania Scope of the Conference The conference primarily focuses on empirical and theoretical work in the fields of economics, business, finance, and management. Given the research diversity of the 12 faculties of the Bucharest University of Economic Studies, it encompasses a broad spectrum of topics within these areas, encouraging interdisciplinary research and innovative approaches. Statement of Purpose: Fostering Academic Exchange: ICESS aims to serve as a dynamic forum for the exchange of ideas, research findings, and methodologies in economics and social sciences. Encouraging Innovative Research: By bringing together diverse perspectives, the conference seeks to stimulate innovative research and thought leadership in its core areas. Building Professional Networks: It provides an invaluable opportunity for participants to network, collaborate, and form partnerships with international peers and experts. Promoting Academic Growth: Through its publication series, ICESS aims to contribute to the academic growth of participants by offering a prestigious platform for their research to be recognized and cited. Volume 2019 Collaborative Research for Excellence in Economics and Social Sciences, ISBN 9788366675322 Volume 2020 Innovative Models to Revive the Global Economy, ISBN 9788395815072 Volume 2021 Resilience and Economic Intelligence Through Digitalization and Big Data Analytics, ISBN 9788366675704 Volume 2022 Fostering recovery through metaverse business modelling, ISBN 978-83-67405-07-2 The world today is vastly different than what it was even a few decades ago, as a result of advances in technology, globalization, and societal changes. Recently, particular attention has been given to sustainable development raising the question of how to drive economic growth in a responsible manner by harnessing technology's potential while accounting for diverse national perspectives. In 2015, the United Nations agreed upon 17 Sustainable Development Goals (SDGs) aimed to transform our world by 2030. However, without the support of stakeholders from government, business and civil societies, the SDGs are only aspirations. In light of these developments, ICESS 2023 provides a space for all those interested in Economics and Social Sciences to discuss and exchange research ideas for increasing economic performance while improving our quality of life and meeting the needs of future generations. We welcome both empirical and theoretical work that is broadly consistent with the conferenc